Medical abbreviations & normal ranges : survival guide - Jones, Helen, RGN (Nursing & health survival guides., 2019)
Part of the skill of nursing and healthcare involves being able to decipher and understand the meanings of results and abbreviations. Fully updated, this second edition is a handy survival guide which will supply you with up-to-date information and help you understand this language, so that you can provide appropriate holistic care to your patients.